2017
DOI: 10.7448/ias.20.1.21407
|View full text |Cite
|
Sign up to set email alerts
|

Integrated HIV care and service engagement among people living with HIV who use drugs in a setting with a community‐wide treatment as prevention initiative: a qualitative study in Vancouver, Canada

Abstract: Introduction: Social-structural inequities impede access to, and retention in, HIV care among structurally vulnerable people living with HIV (PLHIV) who use drugs. The resulting disparities in HIV-related outcomes among PLHIV who use drugs pose barriers to the optimization of HIV treatment as prevention (TasP) initiatives. We undertook this study to examine engagement with, and impacts of, an integrated HIV care services model tailored to the needs of PLHIV who use drugs in Vancouver, Canada – a setting with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…As PWUD often contend with substantial contextual barriers to engagement in HIV treatment and care, including criminalization, stigma, discrimination, poverty and housing instability, support interventions that are responsive to these vulnerabilities may be more likely to promote the successful management of HIV and decrease risk of onward transmission [63,64]. For example, recent studies have found that complementing TasP initiatives with low-barrier programs that are tailored to the specific needs of PWUD and address multiple social and structural barriers to care simultaneously may help to promote ART adherence and VL suppression [63,64]. Thus, such programs should be scaled up as part of broader TasP-based efforts, and future research should continue to investigate how these may be optimized to better facilitate engagement and retention in HIV care among PWUD.…”
Section: Discussionmentioning
confidence: 99%
“…As PWUD often contend with substantial contextual barriers to engagement in HIV treatment and care, including criminalization, stigma, discrimination, poverty and housing instability, support interventions that are responsive to these vulnerabilities may be more likely to promote the successful management of HIV and decrease risk of onward transmission [63,64]. For example, recent studies have found that complementing TasP initiatives with low-barrier programs that are tailored to the specific needs of PWUD and address multiple social and structural barriers to care simultaneously may help to promote ART adherence and VL suppression [63,64]. Thus, such programs should be scaled up as part of broader TasP-based efforts, and future research should continue to investigate how these may be optimized to better facilitate engagement and retention in HIV care among PWUD.…”
Section: Discussionmentioning
confidence: 99%
“…While food provision can provide other benefits (e.g. the mitigation of hunger (24) (a physical sensation experienced by those with severe FI) (46) , entry points to health-care services (25) , promotion of social interactions (41,47) and support for development of daily routines (25,45) ), the root driver of FI in resource-rich settings is inadequate financial resources (43,(48)(49)(50) . Our study further demonstrates this as FI remains prevalent among DPC clients despite the provision of food.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the food programme at the DPC can be conceptualized within the organization's broader harm reduction mandate, which aims to improve health and reduce health-and drug-related harms (21,41,45) . For example, the food programme at the DPC has been shown to be an integral element of the Centre and a primary access point for individuals interacting with the space (25,45) . Overall, the benefits of integrated care models that include food provision must consider how programming may positively impact clients through a harm reduction approach, even if experiences, such as FI, remain prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That HIV-seropositive PWID were more likely to engage in HCV care may be partially attributable to HIV care facilities which are operating under an integrated care model. 30 Previous research has demonstrated the importance of integrated care models on mitigating barriers to HCV care for HIV-seropositive populations. For example, a recent retrospective review of HIV/HCV co-infected patients in New York found that HCV therapy can be safely integrated into HIV primary care settings with encouraging SVR rates (92%).…”
Section: Discussionmentioning
confidence: 99%